Fractional Differential Equation of LC and LR Electrical Circuit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The fractional derivative isused to calculate the current and charge at any time t in LC,RC and LR circuits by using Laplace Transform of fractional derivatives.